Media Massa Dalam Komunikasi Pembangunan - Hendra, Tomi (Jurnal at-Taghyir, 2019)
Abstract: In the current era of technology, the development of society in social life isvery dependent on mass media, where mass media has a very important role in thismatter. One of the important roles of mass media for the community is as a provider ofinformation, education, and entertainment for the community so that in this way thecommunity is motivated, affected and strives to change the mindset and perspective inlife. In addition, the presence of mass media greatly helps the development process inthe lives of social communities. Along with technological advancements that are closelyrelated to mass media, it cannot be denied that the growth of people's lives will also bemore complete. With the development of mass media at this time the community is ableto respond and be smarter towards the reality around the effects of the growth of thedynamics of their lives.Keywords: Mass Media in Development communicationAbstrak: Di Era teknologi saat ini, perkembangan masyarakat dalam kehidupan sosialsangat tergantung akan media massa, dimana media massa sangat memiliki peran dalamhal tersebut. Salah satu peran penting media massa bagi masyarakat yaitu sebagaipemberi informasi, pendidikan, dan hiburan bagi masyarakat sehingga dengan haldemikian masyarakat termotivasi, terpengaruh dan berusaha untuk merubah pola pikirserta cara pandang dalam kehidupan. Selain itu kehadiran media massa sangatmembantu proses pembangunan dalam kehidupan masyarakat sosial. Seiring dengankemajuan teknologi yang erat hubungannya dengan media massa tidak dapat dipungkiribahwa pertumbuhan kehidupan masyarakat juga akan semakin lengkap. Denganperkembangan media massa saat ini masyarakat mampu merespon dan bisa lebih cerdasterhadap realitas yang ada di sekitar efek dari pertumbuhan dinamika kehidupannya.Kata kunci: Media Massa Dalam komunikasi Pembangunan